PENINGKATAN KECERDASAN SPIRITUAL MELALUI METODE ROLE PLAYING UNTUK ANAK USIA DINI - Badiah, Umi Kulsum Riadul; Elshap, Dewi Safitri (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
The objective of this research was to understand comprehensively the effort to improving the spiritual student of RA Albidayah. The method that have been used in aim to improve spiritual quotient is role play. The data were collected trough participant using interview, observation and test. The data analysis and interpretation indicates that the role play method can be used to improv the spiritual student of RA Albidayah. The role play that have been use in this research have three stages which are preparation, execution, evaluation and discussion. The findings lead to the recommendation for the teacher to use the role play method in aim to improve the spiritual quotient in the RA Albidayah